Scanning activity in elite youth football players - Aksum, K. M.; Pokolm, M.; Bjørndal, C. T.; Rein, R.; Memmert, D.; Jordet, G. (Journal of Sports Sciences, 2021)
The purpose of this study was to analyse the scanning behaviour of elite youth football players across different playing positions and age groups during high-level matches. Data was obtained by filming the 2018 UEFA European U17 and U19 Championship semi-finals and finals. A total of 53 outfield players from the four teams that reached the finals were analysed in both their respective semi-final and final matches, resulting in a total of 1686 attacking play situations. Ecological psychology provided us with the theoretical rationale for the study and informed our research hypotheses and interpretations. We found that U19 players performed more scans than U17 players. A positive relationship between scan frequency and pass success was also found. The results further suggest that opponent pressure and pitch position are both critical contextual factors that may influence scanning behaviour. In addition, central midfielders and central defenders were found to have higher scan frequencies than players in other positions. Our results support and extend previous research, suggesting that playing positions and age groups are important factors that impact visual perception and specifically scanning in football. Potential implications for coaches and recommendations for future studies are discussed.